Oxidative stress and antioxidant modulation in cervical infection by the human papillomavirus - Tatiana Mugnol Schöffel; Lara Kochenborger; Taiana Pedrotti; Nathália Billig Garces; Vanessa Jung Ferreira Flores; Janaina Coser (Cadernos Cajuína)
Human papillomavirus (HPV) infection is the main risk factor for cervical cancer. However, other cofactors are involved in the development of cervical carcinogenesis, such as oxidative stress, and can contribute to the persistence of HPV infection in the epithelium and to its integration into the cell genome. The objective of this study was to assess markers of oxidative stress in cervical samples from women infected with cervical HPV, with or without cytological abnormalities. Cytopathological exams, molecular detection of HPV, and markers of oxidative stress of cell samples from the cervix of 35 women were assessed. The HPV-B group exhibited higher levels of TBARS, GSH, GST, and CP compared to the CG and HPV-A groups, while CAT levels were similar across all groups. CP concentrations were lower in the HPV-A group. Pearson’s correlation analysis showed a positive correlation between CP and GST in the CG group, CP and TBARS in the HPV-A group, and GSH and TBARS in the HPV-B group, highlighting distinct oxidative stress profiles among the groups. The results revealed that women infected by HPV with abnormal cervical cells exhibited higher lipid peroxidation and protein oxidation, although an antioxidant response was also observed.